Contemporary Features and Development Prospects of the Russian Criminal Legislation - IVANOVICH, Gladkikh Viktor (Journal of Advanced Research in Law and Economics; Vol 7 No 8 (2016): JARLE Volume VII, Issue 8(22), Winter 2016, 2017)
The article deals with the legislative problems of drafting Russian criminal justice standards. The problems concern either extreme generality (abstractedness) of the criminal rules inherent in the Romano-Germanic law system, or conversely, in the fragmentation of rules of general effect on specific formulations that introduces new precedents to domestic criminal law. The author appeals to avoid the noted extremes when drafting the new Criminal Code of the Russian Federation (RF), which is underway for two consecutive years now.